2018
DOI: 10.1016/j.tiv.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Variation in doses and duration of particulate matter exposure in bronchial epithelial cells results in upregulation of different genes associated with airway disorders

Abstract: Exposure to particulate matter < 2.5 μm (PM2.5) is associated with a variety of airway diseases. Although studies have demonstrated that high doses of PM2.5 cause cytotoxicity and changes to gene expression in bronchial epithelial cells, the effect of lower doses and repeated exposure to PM2.5 are less well studied. Here, we treated BEAS-2B cells with varying doses of PM2.5 for 1–7 days and examined the expression of a variety of genes implicated in airway disorders. At high doses, PM2.5 increased the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…PM 2.5 was isolated from ambient air pollution collected in Beijing, China from 19–21 January 2015 as previously described ( 20 ). Low volume manual samplers placed on the rooftop of Peking University School of Public Health collected PM 2.5 over a 24-h period on 90 mm Emfab filters, which are made of borosilicate fibers reinforced with woven cloth and bonded with polytetrafluoroethylene (TX40HI20WW, part #7234, Pall Company, Beijing Office, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PM 2.5 was isolated from ambient air pollution collected in Beijing, China from 19–21 January 2015 as previously described ( 20 ). Low volume manual samplers placed on the rooftop of Peking University School of Public Health collected PM 2.5 over a 24-h period on 90 mm Emfab filters, which are made of borosilicate fibers reinforced with woven cloth and bonded with polytetrafluoroethylene (TX40HI20WW, part #7234, Pall Company, Beijing Office, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown that epithelial cells under these conditions persistently release inflammatory cytokines, develop epigenetic changes, and undergo epithelial–mesenchymal transition ( 17–19 ). Our laboratory has shown that repeated exposure to low-concentrations of PM 2.5 over seven days resulted in the upregulation of many genes that were not observed after a single exposure to PM 2.5 ( 20 ). However, a full transcriptomic analysis of this treatment protocol—along with a comparison with higher concentrations and short-term exposure—has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, a high volume air sampler with a pump flow rate of 1.13 m 3 /min was placed on the rooftop of the School of Public Health Building of Peking University in Beijing, China to collect PM 2.5 . The daily PM 2.5 samples were collected on 90 mm Emfab filters (TX40HI20WW, part #7234, Pall Company, Beijing Office, Beijing, China) (Tripathi et al, 2018). To extract PM 2.5 , the filters were cut up into small pieces and placed in 90 ml sterile ultrapure water, then sonicated for total 2 h with every 20 min gently shaking the beaker at constant temperature.…”
Section: Pm 25 Collection and Preparationmentioning
confidence: 99%
“…Airway epithelial cells are able to modulate allergic airway inflammation by their ability to produce a variety of inflammatory mediators including the alarmins IL-33, IL-25 and TSLP, critical for driving type 2 inflammation in the lung tissue. In the human bronchial epithelial cell line BEAS2B, TSLP expression is induced by particle matter (PM) with a diameter <2.5 µm (PM 2.5 ) in an AhR-dependent pathway [ 93 ]. These data are in agreement with the ability of AhR to bind alarmin promoters and activate their transcription [ 30 ].…”
Section: Ahr and Its Deleterious Effects In Experimental Asthmamentioning
confidence: 99%